2019
DOI: 10.22153/kej.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Drilling Parameters of Aluminum Alloy Based on Taguchi Method

Abstract: This paper focuses on the optimization of drilling parameters by utilizing “Taguchi method” to obtain the minimum surface roughness. Nine drilling experiments were performed on Al 5050 alloy using high speed steel twist drills. Three drilling parameters (feed rates, cutting speeds, and cutting tools) were used as control factors, and L9 (33) “orthogonal array” was specified for the experimental trials. Signal to Noise (S/N) Ratio and “Analysis of Variance” (ANOVA) were utilized to set the optimum control facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The roughness manipulation affects the quality of the mechanical and structural components, not only in the visual aspect, but also in the wear and lubrication behavior, friction coefficient, corrosion and fatigue resistance, heat transfer, load transmission, adhesion of coatings and light reflection [7][8][9] . Many tribological studies are being carried out to understand the influence of the machining process parameters, and if possible, manipulate them to obtain surfaces with satisfactory characteristics 10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roughness manipulation affects the quality of the mechanical and structural components, not only in the visual aspect, but also in the wear and lubrication behavior, friction coefficient, corrosion and fatigue resistance, heat transfer, load transmission, adhesion of coatings and light reflection [7][8][9] . Many tribological studies are being carried out to understand the influence of the machining process parameters, and if possible, manipulate them to obtain surfaces with satisfactory characteristics 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the arithmetic average parameter R a is the most used in industry and scientific studies, mainly in conventional machining processes. It is ideal to relate the effect of the cutting parameters with the surface finish, from the point of view of variations in height and depth of roughness 7,12,13 . Mathematically, the R a parameter represents the absolute average of all heights measured along the evaluation length.…”
Section: Introductionmentioning
confidence: 99%
“…Nine tests have been performed and the work procedures have been presented in the flow chart as shown in figure 4. As seen in the Table (5), one parameter changed at three different levels in each test, while the other parameters remained unchanged [2,[4][5][6][7][8]11,[15][16][17][18].…”
Section: Experimental Design and Selection Of Cutting Parametersmentioning
confidence: 99%
“…Apart from the studies on aluminium alloy Al7075, Uddin et al [16] studied the drilling of Al6061 and concluded that the burr formation and roundness error were mainly affected by varying the feed rate. Haleel [17] worked on the optimization of process parameters using the Taguchi method for minimum surface roughness in the drilling process of Al5050. The results showed that tool diameter was the most significant factor that affected the surface roughness following the feed rate and cutting speed.…”
Section: Introductionmentioning
confidence: 99%